Cost and budget impact of mass drug administration compared to expanded school-based targeted preventive chemotherapy for soil-transmitted helminth control in Zamboanga Peninsula, the PhilippinesResearch in context - John Paul Caesar delos Trinos; Luc E. Coffeng; Fernando Garcia, Jr.; Vicente Belizario, Jr.; Virginia Wiseman; Caroline Watts; Susana Vaz Nery (The Lancet Regional Health. Western Pacific, 2024)
Summary: Background: School-based targeted preventive chemotherapy (PC), the primary strategy for soil-transmitted helminth (STH) control, typically focusing on primary schoolchildren, was expanded to secondary school students in the Philippines in 2016. This program still excludes adults, who may also suffer from considerable morbidity and can be a significant reservoir of infection. Mass drug administration (MDA), where the entire population is treated, would bring additional health benefits but will also increase implementation costs. The incremental cost of implementing MDA for STH control compared to expanded school-based targeted PC, however, is unknown. Methods: A cost survey was conducted in Zamboanga Peninsula region in 2021 to estimate the economic and financial cost of implementing MDA compared to the expanded school-based targeted PC from a government payer perspective. A budget impact analysis was conducted to estimate the financial cost to the government of implementing MDA over a five-year timeframe. Monte Carlo simulation accounted for uncertainty in cost estimates. Costs were reported in 2021 United States Dollars ($). Findings: The economic cost of MDA was $809,000 per year (95% CI: $679,000–$950,000) or $0.22 per person targeted (95% CI: $0.19–$0.26), while the expanded school-based targeted PC would cost $625,000 (95% CI: $549,000–$706,000) or $0.57 per person targeted (95% CI: $0.50–$0.64). Over five years, the financial cost to the government for MDA would be $3,113,000 (95% CI: $2,475,000–$3,810,000); $740,000 (95% CI: $486,000–$1,019,000) higher than expanded school-based targeted PC. Interpretation: Implementing MDA in the region will increase the economic and financial costs by 29% and 31%, respectively, when compared to expanded school-based targeted PC. Implementing MDA would require the Department of Health to increase their total expenditure for STH control by 0.2% and could be key in addressing the ongoing STH burden. Funding: The project was funded by the Australian Centre for the Control and Elimination of Neglected Tropical Diseases (NHMRC GA19028), and JPCDT was supported by a UNSW Scientia PhD Scholarship. SVN is funded by an NHMRC Investigator Grant (APP 2018220).